In honorem et memoriam Simon J. Keay, Adlectus Inter Hispanos (1954–2021) - Rodà de Llanza, Isabel (Madrider Mitteilungen, 2021)
In honorem et memoriam Simon J. Keay, Adlectus Inter Hispanos (1954–2021).